Studi Literatur Potensi Binahong (Anredera cordifolia) dalam Pengobatan Luka - Nasution, Jamilah; Ramadhani, Citra Suci; Marianti, Marianti (Mahesa Research Center, 2024)
Binahong (Anredera cordifolia) is a medicinal plant that has long been used in traditional medicine to heal wounds and various other health conditions. This study aims to review the therapeutic benefits of Binahong in wound healing through an analysis of recent scientific literature. The method used in this research is a literature review, where data were collected from various scientific journals discussing the bioactive components and pharmacological effects of Binahong. The analysis results show that Binahong contains flavonoids, saponins, and alkaloids that have anti-inflammatory, antioxidant, antibacterial, and analgesic activities. Flavonoids such as quercetin and kaempferol reduce oxidative stress and inflammation, while saponins enhance collagen production and tissue regeneration. Alkaloids provide analgesic effects that reduce pain in wounds. Clinical studies also indicate that topical application of Binahong extract accelerates wound healing and reduces the risk of infection.